Deliberate behavior modelling of teacher education faculty in integrating gender and development concepts among higher education learners - Michael Angelo A. Legarde; Ivy M. Nazareth; Jason V. Chavez; Alprince King A. Biri; Erwin B. Berry; Kier P. Dela Calzada; Analiza B. Calles (Environment and Social Psychology, 2025)
This qualitative study examined how teacher education faculty in selected Philippine higher education institutions deliberately integrated Gender and Development (GAD) concepts and modeled gender-responsive behavior within and beyond the classroom. Using semi-structured interviews with sixteen (16) purposively selected faculty members from Palawan Province, Biliran Province, Zamboanga City, and Surigao del Sur, Philippines, the study investigated their instructional strategies, motivations, and lived experiences in promoting gender inclusivity. Guided by Feminist Pedagogy and Social Gender Theory, the analysis revealed that faculty members embedded GAD principles through contextualized course content, reflective activities, and discussions that challenged stereotypes and encouraged empathy. Findings indicated that deliberate modeling was evident in the use of inclusive language, equitable classroom interactions, and immediate responses to gender bias or discrimination. Personal encounters with gender inequality, commitment to transformative education, and adherence to institutional mandates emerged as primary motivators for GAD integration. The study concluded that effective gender responsiveness was achieved not merely through curricular compliance but through consistent behavioral modeling that humanized instruction and fostered inclusive learning environments. Faculty behavior served as the most influential medium for translating GAD principles into practice, thereby advancing institutional culture and strengthening gender equality in higher education.